Replica. Lyra ; Replica. Gemma - Oliver, Lauren, 1982- (Harper, an imprint of HarperCollinsPublishers, 2016)
"Replica is a "flip book" that contains two narratives in one, and it is the first in a duology. Turn the book one way and read Lyra's story; turn the book over and upside down and read Gemma's story ... Lyra's story begins in the Haven Institute, a building tucked away on a private island off the coast of Florida that from a distance looks serene and even beautiful. But up close the locked doors, military guards, and biohazard suits tell a different story. In truth, Haven is a clandestine research facility where thousands of replicas, or human models, are born, raised, and observed. When a surprise attack is launched on Haven, two of its young experimental subjects--Lyra, or 24, and the boy known only as 72--manage to escape. Gemma has been in and out of hospitals for as long as she can remember. A lonely teen, her life is circumscribed by home, school, and her best friend, April. But after she is nearly abducted by a stranger claiming to know her, Gemma starts to investigate her family's past and discovers her father's mysterious connection to the secretive Haven research facility. Hungry for answers, she travels to Florida, only to stumble upon two replicas and a completely new set of questions"--From publisher's website.